Development and Characterization of EST-SSR Markers From RNA-Seq Data in Phyllostachys violascens - Cai, Kai; Zhu, Longfei; Zhang, Keke; Li, Ling; Zhao, Zhongyu; Zeng, Wei; Lin, Xinchun (Frontiers in Plant Science, 2019)
Bamboos are woody grass species containing important economic and ecological values. Lei bamboo (Phyllostachys violascens) is a kind of shoot-producing bamboo species with the highest economic yield per unit area. However, it is difficult to identify different varieties of Lei bamboo based on their morphological characteristics. Microsatellites play an important role in plant identification and genetic diversity analysis, and are superior to other molecular markers. In this study, 18,256 EST-SSRs loci were identified in Lei bamboo transcriptome data. A total of 11,264 primer pairs were successfully designed from unigenes of all EST-SSR loci, and 96 primer pairs were randomly selected and synthesized. Eventually, 54 primer pairs were applied in classification of 16 Lei bamboo varieties and 10 different Phyllostachys species. These primer pairs applied in Lei bamboo varieties showed that polymorphism alleles’ number was between 3 and 12, and in Phyllostachys was between 3 and 20. According to the polymorphism alleles, the phylogenetic tree was constructed, which can successfully distinguish 16 P. violascens varieties and 10 Phyllostachys species. Our study presents abundant EST-SSRs resources which are useful for genetic diversity analysis and molecular verification in bamboo, and suggests SSR markers developed from Lei bamboo are more efficient and reliable than ISSR, SRAP and AFLP markers.